Medication Adherence and Its Associated Factors Among Type II Diabetes Mellitus Patients Presenting to Health Centres in Tirupati, Andhra Pradesh, India - Ajeetha B; Anju Damu Ade; Visweswara Rao Guthi; Lalith Meesala (National Journal of Community Medicine)
Background: Diabetes is a swiftly expanding health issue. To avoid or postpone the development of complications, patients need to adherent to their antidiabetic drugs. The objective was to assess medication adherence and to determine the association between medication non-adherence and socio-demographic characteristics, co-morbidities, and self-care and medication practices among Type II Diabetes Mellitus patients.